2010
DOI: 10.1002/anie.201000455
|View full text |Cite
|
Sign up to set email alerts
|

Osmium‐Catalyzed 7‐endo Heterocyclization of Aromatic Alkynols into Benzoxepines

Abstract: The wizard of Os: Regioselective osmium‐catalyzed 7‐endo heterocyclization of aromatic alkynols affords benzoxepines in good yields. The proposed catalytic cycle involves the key formation of osmium–vinylidene complexes via an alkynyl‐hydride–osmium(IV) complex from the starting alkynol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 44 publications
1
51
0
Order By: Relevance
“…[14] However,recent findings have demonstrated that it is ap romising alternative to classical metal catalysts,i n particular for promoting some environmentally friendly reactions. [16] Beller and co-workers recently reported ah ighly regioselective and general osmiummediated hydroformylation of olefins to afford aldehydes. [16] Beller and co-workers recently reported ah ighly regioselective and general osmiummediated hydroformylation of olefins to afford aldehydes.…”
mentioning
confidence: 99%
“…[14] However,recent findings have demonstrated that it is ap romising alternative to classical metal catalysts,i n particular for promoting some environmentally friendly reactions. [16] Beller and co-workers recently reported ah ighly regioselective and general osmiummediated hydroformylation of olefins to afford aldehydes. [16] Beller and co-workers recently reported ah ighly regioselective and general osmiummediated hydroformylation of olefins to afford aldehydes.…”
mentioning
confidence: 99%
“…Recent findings have proved that osmium is a promising alternative to ruthenium catalysts [41] and, although the osmium starting materials are only a few, its stoichiometric chemistry seems to be much richer than that of ruthenium. It is clear that further effort needs to be done in order to find starting materials from commercially available osmium inorganic salts or solvents adducts to reach, or even exceed, the level of development of the ruthenium chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Recently reported are, among others, an asymmetric transfer-hydrogenation of aryl ketones with a chiral iron(II) bis(isonitrile) complex 26 ; an iron-(or cobalt)-catalyzed asymmetric hydrosilylation of ketones with chiral bis(oxazoline) complexes 27 ; regioselective 1,2-hydrosilylation of 1,3-dienes with iron bis-(2-pyridylaldimine) complexes 28 ; an iron-catalyzed dehalogenation of aryl halides 29 ; and inexpensive routes to key N-heterocyclics (including indoles) via iron-catalyzed cyclodenitrogenation of azides 30 . Catalysis with osmium is less diverse, but it is worth mentioning, perhaps, the elusive 7-endo-cycloisomerization to 1,2-dihydro-3-benzoxepines which is far more efficient than under Ru-, Rh-or W-catalysis 31 ; note also the osmium equivalent of Noyori′s homogeneous asymmetric hydrogenation of ketones 32 , affording high enantioselectivities with astonishing TOF values up to 300,000 h -1 . Iridium catalysis has also been in the news again with a transfer-hydrogenative Nalkylation, offering unprecedented substrate scope and being a valuable alternative to classical routes based on hydridoborates 33 ; in addition, there is a report of a simple asymmetric and regioselective conversion of allyl alcohols to prim.…”
Section: Further Trends and Developments In Synthetic Organic Chemistmentioning
confidence: 99%